The Role of Social Media in Enhancing Social Awareness and Community Participation in Education - Rijal, Syamsu; Almaududi Ausat, Abu Muna; Siminto (Indo-MathEdu Intellectuals Journal, 2024)
Education is recognized as one of the fundamental pillars in societal development. The advancement of information technology, particularly social media, has transformed the paradigm in education. Social media offers a broad and easily accessible platform for communities to share knowledge, information, and experiences. This research aims to delve deeper into the role of social media in enhancing social awareness and community participation in education. The research method employed in this study is a literature review using a qualitative approach and descriptive analysis. Data for this research were gathered from Google Scholar for the period 2008-2024. The study findings indicate that social media plays a significant role in enhancing social awareness and community participation in education. Through its ability to disseminate information quickly and widely, social media opens up opportunities to broaden societal awareness of social and educational issues. Furthermore, social media also facilitates active participation in learning and discussions, both in formal and informal contexts